Learning unethical practices from a co-worker: the peer effect of Jose Canseco - Eric D. Gould; Todd R. Kaplan (Institute for the Study of Labor (IZA), 2008)
This paper examines the issue of whether workers learn productive skills from their co-workers, even if those skills are unethical. Specifically, we estimate whether Jose Canseco, one of the best baseball players in the last few decades, affected the performance of his teammates. In his autobiography, Canseco claims that he improved the productivity of his teammates by introducing them to steroids. Using panel data on baseball players, we show that a player's performance increases significantly after they played with Jose Canseco. After checking 30 comparable players from the same era, we find that no other baseball player produced a similar effect. Clearly, Jose Canseco had an unusual influence on the productivity of his peers. These results are consistent with Canseco's controversial claims, and suggest that workers not only learn productive skills from their co-workers, but sometimes those skills may derive from unethical practices. These findings may be relevant to many workplaces where competitive pressures create incentives to adopt unethical means to boost productivity and profits.
Keywords: J24; 330; Peer effects; corruption; crime; externalities; Soziale Gruppe; Soziale Beziehungen; Lernen; Leistungsmotivation; Arbeitsproduktivität; Ethik; Kriminalität; Sport; USA